(untitled) (Indian Journal of Arid Horticulture, 2025)
Guava (Psidium guajava L.) is one of the important fruits of India and ranks fourth in area and production after mango, banana and citrus. The fruits are rich in Vitamin-C, pectin, phosphorus and calcium (Wilson, 1980). The chemical composition of fruits differ with variety, stage of maturity, size and season. Guava is available in plenty during the fruiting season. Its disposal becomes a serious problem particularly in rainy season. Its utilization is very little in processing industry. Only jelly is made from its fruits. But its excellent flavour and nutritive value have a great potential in beverage. The beverage are becoming popular in comparison to synthetic or carbonated drinks. Therefore, the present study was undertaken to exploit its potential in the bevarage industry drinks.